Synthesis and Characterization of Calcium Phosphate Using Two Stages of Process - Anggoro, Achmad Rahditya Viman; Arianti, Rahma Dea Rerindra; Pujiastuti, Caecilia; Sumada, Ketut; Muljani, Srie (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Calcium phosphate, a naturally occurring biomaterial found in human and animal bones and teeth, possesses desirable properties such as strength, biocompatibility, and the ability to stimulate tissue growth. This study investigates the synthesis of calcium phosphate through a precipitation method without calcination. The process involves dissolving raw materials in phosphoric acid, followed by precipitation using KOH as the precipitating agent. The resulting precipitate was then calcined for 3 hours. The calcium phosphate product was characterized using XRF, XRD, and SEM-EDX techniques. The results indicate a Ca-P molar ratio ranging from 1.855 to 2.302, with the predominant phase identified as -calcium pyrophosphate. SEM analysis reveals a plate-like morphology with agglomerated particles ranging in size from 888 nm to 7.79 m. The synthesized calcium phosphate holds potential for various biomedical applications due to its unique properties and composition.